Implementasi Geo-KKP Sebagai Penerapan E-Government di BPN Kantor Pertanahan Kabupaten Bogor I - Mohamad Zein Surya Pandega; Syahrul Rivaldi; Silmi Afina Aliyan (BULLET : Jurnal Multidisiplin Ilmu, 2023)
In 2010, the Ministry of Agrarian Affairs/National Land Agency launched a land administration system known as the Computerized Land Office (KKP), then underwent development and changed its name to Geo-KKP, where this system allows integration between textual and spatial data and is able to minimize error in mapping. Textual data is data in the form of text that describes the physical condition of the land, such as location, location, land condition, and land area. The purpose of this study was to analyze what obstacles were faced by the National Land Agency of Bogor Regency I in implementing Geo-KKP to validate textual data and Geo-KKP as an application of E-Government at BPN Bogor Regency I. The method used in this study was the Qualitative research uses data collection in the form of literature studies and interviews with informants. The results of the study show that the digitalization process is running as it should, supported by the availability of qualified tools and resources in their fields. However, in its implementation, there are still several obstacles, namely the lack of sufficient resources to digitize, resulting in an accumulation of physical files.